Comparison of Knowledge of Women with Gestational Diabetes Mellitus and Healthy Pregnant Women Attending at Hospital in Bangladesh - Monir, Nowshin; Zeba, Zebunnesa; Rahman, Azizur (Journal of Current and Advance Medical Research, 2019)
Background: A very common medical condition during pregnancy is Gestational Diabetes Mellitus (GDM) which has become a global health concern, not only for its higher prevalence, but also because it can be a predisposing factor for type 2 DM and causes other increased health risk for both mother and their offspring in later life. Objective: The objective of the study was to compare knowledge of GDM including source of knowledge, treatment, awareness about GDM and impact of GDM on the baby among mothers with GDM and healthy pregnant mothers. Methodology: The study was a cross-sectional study conducted in Cumilla city from May to October 2016. Eighty-nine participants attending the outpatient department of two hospitals and one antenatal clinic in Cumilla city were selected. A structured questionnaire and in-depth interview method was used to obtain data. Result: Significant difference has been found in knowledge between GDM patients and normal pregnant women regarding source of knowledge (p=0.01), treatment of GDM (p=0.000), risk factors of GDM (p=0.01), problems in managing GDM (p=0.003), nutrition maintenance (p=0.006) and physical exercise (p=0.000). No significant difference has been found in GDM awareness (p=0.83) and its impact on the baby (p=0.28) in two groups. Awareness of GDM is found to be associated with higher education (p=0.000), family history of DM (p=0.05), meal plan (p=0.03) and maintaining nutrition (p=0.01). Conclusion: Knowledge about GDM is poor among pregnant women, especially among normal pregnant women. Journal of Current and Advance Medical Research 2019;6(1):32-37